AN ANALYSIS OF UNTOUCHABILITY IN MULK RAJ'S NOVEL - Shyam, Kumar Sharma (Journal of Current Research and Review (JCRR), 2022)
This paper analyzes Mulk Raj's novel, which highlights the issue of untouchability in Indian society. The novel portrays the discriminatory behavior of the upper-class people towards the lower or untouchable people. The characters in the novel represent the various facets of Indian society, and through their experiences, the novel showcases the harsh realities of the caste system. The paper examines the different aspects of untouchability, including its impact on the social, political, and economic status of the Dalit community. The study focuses on the character of Bakha, a sweeper, who is the central character of the novel. The paper analyzes how Bakha's experiences represent the dehumanizing treatment that the Dalit community received from the upper-class people. The study also looks at other characters in the novel, including Solini, Charat Singh, and Lakha, who represent different aspects of the social structure. The paper concludes by examining the impact of the novel on the Indian society and the role it played in bringing awareness to the issue of untouchability